The Relationship between Financial Incentives and Perceptions of Student Choice At Private Universities in Egypt - Abdelbary, Alaa; Elmasery, Samer; Ragab, Aiman; Ragheb, Mohamed (IJRDO - Journal of Business Management, 2020)
The purpose of the study was to investigate the role of financial incentives in the student choice of an undergraduate degree granting higher education institution in selected private universities in Egypt. Simple random sampling was used to choose the universities for the study.These Five universities were chosen randomly for the study from total 24 universities: German University, French University, Russian University, British University and Miser University of Science and Technology. The sample consisted of 390 students conveniently selected from the total number of students in those selected institutions. A survey was the main method of data collection. The results of the study reached there is a significant relationship between Financial Incentives and Perceptions of Student Choice.